2000
DOI: 10.1017/s1092852900021623
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Comorbidity Among Anxious and Odd Personality Disorders: The Case of Obsessive-Compulsive Personality Disorder

Abstract: The aim of this study was to examine the pattern of comorbidity among obsessive-compulsive personality disorder (OCPD) and other personality disorders (PDs) in a sample of 400 psychiatric inpatients. PDs were assessed using the Semistructured Clinical Interview for DSM-III-R Personality Disorders (SCID-II). Odds ratios (ORs) were calculated to determine significant comorbidity among OCPD and other axis II disorders. The most elevated odds ratios were found for the cooccurrence of OCPD with cluster A PDs (the “… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 27 publications
2
9
0
Order By: Relevance
“…DSM-5 OCPD traits were also associated with the ICD-11 domains of low disinhibition and negative affectivity (17,21). The finding that OCPD traits overlap with different domains is consistent with work demonstrating that OCPD is comorbid with a number of other PDs including avoidant (52), paranoid (52,53), schizotypal (54), borderline and narcissistic (52) PDs. A dimensional structure for describing maladaptive personality traits may be helpful in addressing the artifactual comorbidity that occurs in a categorical system (13,55).…”
Section: The Clinical Utility Of the Icd-11 Pd Modelsupporting
confidence: 83%
“…DSM-5 OCPD traits were also associated with the ICD-11 domains of low disinhibition and negative affectivity (17,21). The finding that OCPD traits overlap with different domains is consistent with work demonstrating that OCPD is comorbid with a number of other PDs including avoidant (52), paranoid (52,53), schizotypal (54), borderline and narcissistic (52) PDs. A dimensional structure for describing maladaptive personality traits may be helpful in addressing the artifactual comorbidity that occurs in a categorical system (13,55).…”
Section: The Clinical Utility Of the Icd-11 Pd Modelsupporting
confidence: 83%
“…Lifetime prevalence rates for OCPD according to DSM-IV criteria range from 3 to 8 % [6••, 21,22]. In an outpatient population, OCPD was identified as the third most common personality disorder (diagnosed according to DSM-IV criteria) with a point prevalence rate of 8.7 % [23] and in a psychiatric inpatient population as the second most prevalent personality disorder with a rate of 23.3 % (not specified which kind of prevalence) when considering DSM-III-R-criteria [24]. As for sex distribution, some studies demonstrate the same rates for men and women [6••] whereas others indicate higher prevalence rates amongst men than women [25,26].…”
Section: Epidemiology and Course Of Ocpdmentioning
confidence: 99%
“…Studies from non-clinical populations indicate that a lifetime diagnosis of OCPD is moderately common in individuals with 12-month diagnoses of anxiety disorders ( (14 % [41]). Moreover, there is growing evidence for a considerable co-occurrence of OCPD with Cluster A personality disorders, in particular with paranoid and schizotypal personality disorders [16,24,42], which have led to the question whether OCPD should continue to be classified as a Cluster C personality disorder. Finally, it has recently been found that OCPD is very common amongst individuals suffering from medical conditions such as joint hypermobility syndrome/ Ehlers-Danlos syndrome hypermobility type [43] and Parkinson's disease [44].…”
Section: Co-occurrences Of Ocpdmentioning
confidence: 99%
“…In an outpatient population, Zimmerman, Rothschild and Chelminski (2005) found the OCPD being the third prevalent PD (8.7%) after the avoidant PD (14.3%) and the borderline PD (9.3%). In psychiatric inpatients, OCPD was the second most prevalent PD (28.3%; Rossi, Marinangeli, Butti, Kalyvoka, & Petruzzi, 2000).…”
Section: Epidemiology and Coursementioning
confidence: 99%
“…Not surprisingly, given that one of the defining characteristics of OCPD is overconscientiousness and scrupulosity, antisocial PD was diagnosed significantly less frequently in the OCPD group than in the other PD groups. In psychiatric inpatients, Rossi et al (2000) reported a mean of 2.7 PDs per person. The most elevated odds ratios were found for the co‐occurrence of OCPD with paranoid PD and schizoid PD.…”
Section: Epidemiology and Coursementioning
confidence: 99%